Salinity and copper interactive effects on perez's frog Pelophylax perezi - Santos, Bárbara (2018)
The present study was intended to assess the influence of salinity on the effects of copper on 2 life stages of Pelophylax perezi. Single and combined effects of salinity (NaCl) and Cu on survival, malformations, body length, and biochemical markers (catalase [CAT], cholinesterases, lactate dehidrogenase [LDH], and glutathione S-transferase) of individuals were evaluated in a multifactorial design. Two experiments were performed, 1 with embryos and the other with tadpoles. Each of these life stages was exposed to individual and combinations of Cu (0.0-7.4 mg/L and 0.0-2.4 mg/L, respectively) and NaCl (0.0-10.2 g/L and 0.0-7.4 g/L, respectively) concentrations. Copper alone had a higher lethal toxicity to tadpoles (90%; 2.4 mg/L) than to embryos (65%; 7.4 mg/L). Conversely, NaCl alone had a higher lethal toxicity to embryos (100%; 6.9 g/L) than to tadpoles (50%; 7.4 g/L). The 4 lowest tested NaCl concentrations decreased the lethal effects of Cu to embryos and the incidence of malformations, but the same outcome was not observed for tadpoles. Regarding enzymatic activities, although significant interactions between Cu and NaCl were observed for the activity of CAT and LDH in embryo and tadpole, a consistent pattern of NaCl and Cu interactive effects was not observed. The authors' results suggest a life-stage dependence on the effects of exposure to the individual substances or their combination. Also, it was observed that moderate salinity might have a shield effect against Cu lethal toxicity for embryos of P. perezi. These results highlight the need within ecological risk evaluations to characterize the sensitivity of different amphibian life stages to individual chemicals but also their combination with other environmental conditions resulting from climate changes.